Time-Course of Changes in Photosynthesis and Secondary Metabolites in Canola (Brassica napus) Under Different UV-B Irradiation Levels in a Plant Factory With Artificial Light - Lee, Jin-Hui; Shibata, Seina; Goto, Eiji (Frontiers in Plant Science, 2021)
This study aimed to evaluate short-duration (24 h) UV-B irradiation as a preharvest abiotic stressor in canola plants. Moreover, we quantified the expression levels of genes related to bioactive compounds synthesis in response to UV-B radiation. Canola seedlings were cultivated in a plant factory under artificial light (200 μmol m–2 s–1 photosynthetic photon flux density; white LED lamps; 16 h on/8 h off), 25°C/20°C daytime/nighttime air temperature, and 70% relative humidity. Eighteen days after sowing, the seedlings were subjected to supplemental UV-B treatment. The control plants received no UV-B irradiation. The plants were exposed to 3, 5, or 7 W m–2 UV-B irradiation. There were no significant differences in shoot fresh weight between the UV-B-irradiated and control plants. With increasing UV-B irradiation intensity and exposure time, the H2O2 content gradually increased, the expression levels of genes related to photosynthesis downregulated, and phenylpropanoid and flavonoid production, and also total phenolic, flavonoid, antioxidant, and anthocyanin concentrations were significantly enhanced. The genes related to secondary metabolite biosynthesis were immediately upregulated after UV-B irradiation. The relative gene expression patterns identified using qRT-PCR corroborated the variations in gene expression that were revealed using microarray analysis. The time point at which the genes were induced varied with the gene location along the biosynthetic pathway. To the best of our knowledge, this is the first study to demonstrate a temporal difference between the accumulation of antioxidants and the induction of genes related to the synthesis of this compound in UV-B-treated canola plants. Our results demonstrated that short-term UV-B irradiation could augment antioxidant biosynthesis in canola without sacrificing crop yield or quality.